2015
DOI: 10.1007/s12221-015-4931-8
|View full text |Cite
|
Sign up to set email alerts
|

Use of ultrasonic energy for enhancing the dyeing performances of polyamide fibers with olive vegetable water

Abstract: The present study reports the valorization of the olive vegetable water in natural dyeing. HPLC analysis of the phenolic extract obtained from the used olive vegetable water showed that the predominant flavonoid compounds were luteolin and apigenin. Hydroxytyrosol and various phenolic acids were also identified. This abundant waste was used as a possible dye bath for dyeing polyamide fabrics in conventional and ultrasonic techniques. It was found that these synthetic fibers possess high affinity to the olive v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…Grape seeds were collected from the local markets in Baghdad, then washed and left to dry with stirring from time to time to prevent rotting, then finely ground to be used for phenol extraction. Phenols were prepared according to the method described in [10]. 50 g of seed powder was taken, then 500 ml of petroleum ether solvent was added to it at a ratio of 10:1 (solvent: plant) and placed in a Soxhlet device at a temperature of 60 °C for a period of 4-6 hours.…”
Section: Collect Vitis Vinifera Grape Seeds and Prepare The Phenolic ...mentioning
confidence: 99%
“…Grape seeds were collected from the local markets in Baghdad, then washed and left to dry with stirring from time to time to prevent rotting, then finely ground to be used for phenol extraction. Phenols were prepared according to the method described in [10]. 50 g of seed powder was taken, then 500 ml of petroleum ether solvent was added to it at a ratio of 10:1 (solvent: plant) and placed in a Soxhlet device at a temperature of 60 °C for a period of 4-6 hours.…”
Section: Collect Vitis Vinifera Grape Seeds and Prepare The Phenolic ...mentioning
confidence: 99%
“…The use of natural dyes on dyeing process was defined to be very promising. Many successful applications of bio-sourced pigments and dyes were proposed in dyeing field [26][27][28][29][30][31][32]. Several industrial applications were also noted.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been reported on application of different natural dyes on textile fibers. Barberry tree root, cumin seeds, grape leaves and pomace, red cabbage, milkweed leave, Achilleapachycephala flowers, almond shell, pomegranate rinds and wastewater of olive oil production are examples of new sources of natural dyes which have been studied in recent years [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Despite several advantages associated with the use of natural dyes in dyeing textile goods, there is a great need for optimization of natural dyeing processes to fulfill the equipments of today's industry.…”
Section: Introductionmentioning
confidence: 99%